Numerical solution of convection-diffusion problems - Morton, K. W. (Applied mathematics and mathematical computation, 1999)
A comprehensive treatment of the numerical solution of correction diffusion problems. These problems are important in areas such as computational fluid dynamics and are solved by advanced numerical analysis.